AI AND ONLINE DISPUTE RESOLUTION (World Bulletin of Management and Law, 2024)
Legal proceedings are still the most important way of resolving disputes. However, given the volume and nature of new disputes, mostly arising from electronic contracts, the courts are becoming slower and outdated. ODR is an emerging set of technologically-enabled tools and processes for facilitating conflict resolution. ODR is an area of law which uses technology to make it easier for people to settle their differences. It involves negotiation, mediation, arbitration or a combination of these. It is often seen as the online equivalent of Alternative Dispute Resolution (ADR). Artificial Intelligence (AI) refers to simulating human intelligence in machines programmed to think and act like human beings. AI can be applied in various fields, including ODR.1 In this paper, I present a critical assessment of the use of AI-based techniques in ODR.